Evaluación de la producción de forraje de híbridos de maíz para silaje en el Valle Inferior del Río Negro (campaña 2008-2009)) - Miñon, Daniel Pedro; Gallego, Juan Jose; Barbarossa, Raul Antonio; Margiotta, Francisco Andrés; Martinez, Roberto Simon; Reinoso, Lucio (EEA Valle Inferior, INTA, 2021)
EEA Valle Inferior